2012
DOI: 10.1186/1475-2875-11-133
|View full text |Cite
|
Sign up to set email alerts
|

Differential Plasmodium falciparum infection of Anopheles gambiae s.s. molecular and chromosomal forms in Mali

Abstract: BackgroundAnopheles gambiae sensu stricto (s.s.) is a primary vector of Plasmodium falciparum in sub-Saharan Africa. Although some physiological differences among molecular and chromosomal forms of this species have been demonstrated, the relative susceptibility to malaria parasite infection among them has not been unequivocally shown. The objective of this study was to investigate P. falciparum circumsporozoite protein infection (CSP) positivity among An. gambiae s.s. chromosomal and molecular forms.MethodsWi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
2
18
1
Order By: Relevance
“…The CSP positive rate was significantly higher in A. gambiae (12.6%) than A. coluzzii (4.3%) (Wilcoxon rank sum test P-value=0.0384). This is consistent with the earlier study in Senegal ( Ndiath et al , 2011) but differs from a recent survey conducted in Mali ( Fryxell et al , 2012). The study site in Senegal located in the village of Dielmo (13°43'N, 16°24'W) ( Ndiath et al , 2012)) was geographically closer (200km) than Mali sites (>800km) to our collection sites in Guinea-Bissau.…”
Section: Resultssupporting
confidence: 90%
“…The CSP positive rate was significantly higher in A. gambiae (12.6%) than A. coluzzii (4.3%) (Wilcoxon rank sum test P-value=0.0384). This is consistent with the earlier study in Senegal ( Ndiath et al , 2011) but differs from a recent survey conducted in Mali ( Fryxell et al , 2012). The study site in Senegal located in the village of Dielmo (13°43'N, 16°24'W) ( Ndiath et al , 2012)) was geographically closer (200km) than Mali sites (>800km) to our collection sites in Guinea-Bissau.…”
Section: Resultssupporting
confidence: 90%
“…The epidemiological importance of GOUNDRY is not currently known, although in experimental infections, this population is physiologically more permissive than M or S form A. gambiae to infection with P. falciparum (Riehle et al 2011). Because the M and S molecular forms are both primary malaria vectors in sub-Saharan Africa, and rates of natural P. falciparum infection in wild M and S mosquitoes are equivalent (Wondji et al 2005; Ndiath et al 2008; Trout Fryxell et al 2012), Plasmodium-driven selective pressure, if it exists, should be shared among these subgroups. However, in our data, only 1 of the 11 signals of positive selection (that at APL1B ) was shared by two subpopulations (Figure 3), and we found no evidence of non-neutral evolution in any genes in the S-form population.…”
Section: Discussionmentioning
confidence: 99%
“…M/S hybrids are rarely observed in natural settings but several recent studies reported levels of hybridization higher than expected for cryptic species [19], [20], [22], [59], [62], [63], [64] ). Subgroups of An.…”
Section: Discussionmentioning
confidence: 91%
“…Out of the 400 described Anopheles species, less than 20 are capable of transmitting malaria parasites [58]. Some species are more susceptible to Plasmodium infection than others, and even at the population level, their susceptibility differs [21], [22], [59]. The respective role of the different vectors in malaria transmission needs to be clarified, and our assay will be useful to provide accurate estimation of the entomological inoculation rate (EIR) of each vector species or populations; EIR being the key parameter to measure malaria transmission intensity in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation